Educação popular na comunidade Viva Deus: mística popular, amorosidade e dialogicidade para o fortalecimento da luta pela conquista da terra - LIRA, Marcos Moreira (2021)
The following research was carried out in Comunidade Viva Deus in a camp that since 2003 has been fighting for agrarian reform on Estrada Padre Josimo in Imperatriz/MA in which the Teaching Group, Research and Extension in Popular Education – GEPEEP has been contributing to the community's struggle since 2015 with other social movements. Our main objective was to understand how Mysticism and Popular Education contribute to the construction process of dialogicity, lovingness, and for the strengthening of the struggles and resistances for the conquest of the Earth in the Viva Deus Community. Thus, we use the methodology in Popular Education based on Paulo Freire (1968, 1980, 1996) and Mística em Bogo (2008) for the intervention processes, being action research based on Thiollent (2009) and qualitative research based on Minayo (2001) for analysis of results. The results were a greater union between the subjects of the Viva Deus Community, in addition to strengthening a critical and political awareness of the condition of subjects oppressed by a capitalist system and the autonomy to create collective alternatives to overcome situations-problems-challenges that prevent them from conquering the land, thus promoting a greater exchange with other social movements that defend the countryside and thus strengthening their struggle. With this practical and theoretical experience, Popular Mysticism becomes a child of Popular Education and Mysticism, being a powerful instrument that strengthens the struggle for the land of the Viva Deus Community, in the sense that it promotes love and dialogicity, facilitating the survey of situations-problems-challenges and an objective and subjective critical reflection that generally leads them to an alternative solution, be intervening with songs, dances, collective texts, poetry, craftsmanship, drawings, reading, acting, ornamentation, logistics, organization and the simple fact of resisting, live and survive.